Obtention and characterization of a hybrid nanocomposite monolith by sol–gel process - Legarto, Maria Celeste (2021)
A monolithic porous composite was synthesized by sol–gel process, containing the maximum and significant amount of bentonite that allows its use as a filter bed in aqueous effluents treatment. This process is able to apply on an industrial scale. The bentonite used was an efficient adsorbent for various contaminant molecules in aqueous media when is operated in a batch stirred tank, but presents difficulty in the separation stage of suspended particles. In this laboratory-scale work, cylindrical monoliths of 9 cm length by 2 cm diameter were made that can be used as a filter bed. The primary composite, silica-resin, was prepared by the sol–gel precursor mixture of the partially hydrolyzed tetraethylorthosilicate and a phenol-formaldehyde resin. Bentonite was added to the pre-gelling, obtaining the silica-resin-bentonite composite, made up the gel which is then dried and cured at 270 °C. The different composites mineralogical and structurally were evaluated. The preliminary performance of the developed bentonite filter bed showed almost 90% adsorption of diphenylamine, a commercial agrochemical widely used as anti-antiscaldant in postharvest treatment of fruit, and showed that the bentonite conserves its adsorption capacity and controls the swelling of the interlayer space which encourages further research studies applied to water treatment.